Let’s not Miss the Opportunity to Improve Rare Disease Reporting Through ICD-11 Implementation - Miroslav ZVOLSKÝ; Šárka DAŇKOVÁ; Marie VIKDAL; Carine ALSOKHN; Robert JAKOB; Milan BLAHA (Applied Medical Informatics)
The identification of rare diseases in health data is crucial for their epidemiological definition. Beyond the existing terminology system ORPHAcodes, we describe the possibilities of the 11th revision of the International Classification of Diseases. We analyzed the linkages of ORPHAcodes to ICD-11 items with only 376 items lacking unique representation in ICD-11. ICD-11 can be used to identify most rare diseases in administrative data.